2005
DOI: 10.1021/bc040244z
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Postgrafted Colloidal Particles for Gene Delivery

Abstract: Surface modification of cationic lipoplexes has been carried out by means of a postgrafting reaction. The original lipoplexes described comprise a cationic lipid, a neutral lipid, poly(ethylene glycol)-cholesterol (with or without a targeting ligand) and DNA. Modifying their surface via a chemical, postgrafting reaction did not alter their size (approximately 100 nm) nor their ability to compact DNA, but did give a reduced zeta potential (approximately 0 mV) to afford surface neutral particles. With the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…However, the positive charges of the cationic lipids induce a poor efficiency in vivo [3], [4] as lipoplexes are captured by opsonins or other physiological components, hence resulting in a low circulation time [5]. Numerous studies have been undertaken to improve serum resistance by masking or suppressing the cationic charges [6], [7]. Alternative delivery systems have been introduced, using non electrostatic interaction with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive charges of the cationic lipids induce a poor efficiency in vivo [3], [4] as lipoplexes are captured by opsonins or other physiological components, hence resulting in a low circulation time [5]. Numerous studies have been undertaken to improve serum resistance by masking or suppressing the cationic charges [6], [7]. Alternative delivery systems have been introduced, using non electrostatic interaction with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the second strategy involves the covalent attachment of the shielding polymer to preformed non-viral nanocomplexes [88]. Since PEGylation may prevent endosomal escape, different groups are currently developing several strategies in which the nanocomplexes are deprived of their PEG-chains outside the cellor in acidifying endosomal compartments [89].…”
Section: Pegylation As Methods For Shielding Nanocomplexesmentioning
confidence: 99%
“…[23][24][25] This information suggested that the liposomal hydration level is another important factor affecting its association with the cell membrane. Here we examined the effect of MEL-A and Tween 80 on hydration levels of liposomes and lipoplexes.…”
Section: The Hydration Level Of Liposomes and Lipoplexes As Monitoredmentioning
confidence: 97%